Development of Stages of The Implementation of The Environmental Monitoring Program - Rahimova Nazila; Abdullayev Vugar; Abbasova Vasila (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
The object of the research is environmental monitoring, which allows to present the current situation about the environment. The monitoring program aims to gather information for the decision-making process. This article describes environmental monitoring and highlights its main goals and objectives. This article describes the properties of the environmental monitoring object. The main components of environmental monitoring are also considered here. The database and analytical data-processing tools are main components of environmental monitoring. In addition, this article considers the structure of environmental monitoring. Next, environmental monitoring functions were considered. This article also provided a classification of monitoring systems. One problem is the development of the most appropriate algorithm for implementing environmental monitoring. The article is devoted to the development of software modules of environmental information systems that perform geographic and environmental data processing. There are software modules designed for centralized operation of data (data entry, editing, deleting, etc.), the conceptual types of GIS, the goals and functions of environmental monitoring, and these are taken into account in the existing system. The monitoring system should also have a good search tool, which is also described in this article. The search tool is described using SQL and Delphi. The research used decision-making methods. This article describes the stages of development of an environmental monitoring program. The research identified the inputs and outputs of the environmental monitoring programme, as well as its objects and the relationship between them. The results obtained in the future will be useful for improving the decision-making of authorized persons.